Modeling of Lithuanian cohort survivorship - Rasa Mišeikytė (Lietuvos Matematikos Rinkinys)
Survival distributions, arising from six parametrical families were fitted to the mortality experience of Lithuanian cohorts, born in 1928–1935 and 1946–1966 years.